Bald on Record Strategies Used by the Characters in Secret Society of Second-Born Royals Movie - Shofa, Ais Lu’luatus; Jannah, Roudlotul (ICONELT, 2024)
This study examines the bald-on-record strategies used by the characters in the movie Secret Society of Second-Born Royals. The research employs a descriptive qualitative approach, with data consisting of the utterances spoken by the characters in the movie. The researcher identifies, classifies, and discusses the data based on different bald-on-record strategies. Brown and Levinson’s (1987) theory is used to analyze these strategies. The study found that the characters frequently employed the strategy of maximum efficiency when speaking to others, especially when giving instructions in urgent situations. Additionally, the characters mostly used task-oriented or paradigmatic forms of instruction, typically when giving commands about what they need. Moreover, the characters used the strategy of farewells to end conversations and shorten communication time with the listeners. In these instances, the speakers did not minimize the face-threatening acts (FTAs) by disregarding the positive face. This indicates that the speakers did not prioritize the listeners’ self-esteem during communication.